Principles of anatomy and physiology - Tortora, Gerard J; Derrickson, Bryan (Hoboken, NJ : John Wiley & Sons, 2010)
This edition of 'Principles of Anatomy and Physiology' maintains the superb balance between structure and function. It continues to emphasize the correlations between normal physiology and pathophysiology, normal anatomy and pathology, and homeostasis and homeostatic imbalances. The acclaimed illustration program is also even better along with the redevelopment of many of the figures depicting the toughest topics to grasp. -- Publisher's website
An introduction to the human body -- The chemical level of organization -- The cellular level of organization -- The tissue level of organization -- The integumentary system -- The skeletal system: bone tissue -- The skeletal system: the axial skeleton -- The skeletal system: the appendicular skeleton -- Joints -- Muscular tissue -- The muscular system -- Nervous tissue -- The spinal cord and spinal nerves -- The brain and cranial nerves -- The autonomic nervous system -- Sensory, motor, and integrative systems -- The special senses -- The endocrine system -- The cardiovascular system: the blood -- The cardiovascular system: the heart -- The cardiovascular system: blood vessels and hemodynamics -- The lymphatic system and immunity -- The respiratory system -- The digestive system -- Metabolism and nutrition -- The urinary system -- Fluid, electrolyte, and acid-base homeostasis -- The reproductive systems -- Development and inheritance
Includes index
Includes bibliographical references and index
Keywords: Human physiology -- Outline